Espacios interculturales, espacios transculturales y transliteraturas (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Globalization challenged the notion of borders redefining migration, confinement and (im)mobility. Nowadays, the “self” and the “other” meet in a “neutral” space where geographies and landscape merge hosting the dialogue in a welcoming space that while defying a definite description opens itself up for exploration. Our world is characterized by pluralities, by spaces that are less and less defined, by messages that circulate in an undefined cyberspace in multiple languages, in exchanges that are closer and closer to a simultaneous dialogue where words and thoughts that represent multicultural spaces escape being defined as a geographical space while nonetheless painting a unique landscape. I will explore these concepts as I will analyze the transliterary process of migration of stories, cultures and cultural artifacts centering my study in the transcultural space. I will analyze this figurative and objective geographical space. I will study how the story after being confined to a class perception, to cultural stereotypes thus being held immobile, then thanks to the creation of a transliterary space the story migrates and participates in the globalized dialogue that transcends the literary realm of origin. This literary and cultural migration take place in a landscape that represents the transitional aspect of the literary transaction creating a unique geographical landscape and space that I will explore in detail.
Keywords: transcultural space; globalization; transliterature; autochtonous territory; reconfiguring intercultural space